Hanlam: Marriage payment in the 21st Century: A Case Study from Wokha Town - W, Mhabeni; Pongen, Dr. Moameren (International Journal of Humanities and Education Development (IJHED), 2023)
Marriage is one of the oldest social institutions in human society. During this occasion, some marriage payments are made in the form of bride price, dower, and dowry. In the Lotha community, a marriage payment, "Hanlam" is practiced. Hanlam is different from any of the marriage payments mentioned above. Thus the study's main objective is to find out the relevance of the Hanlam practiced among the Lotha community and its impact on women's rights. The paper is descriptive, where the respondents were selected based on purposive sampling. Altogether 50 couples from Wokha town were interviewed. The study found that Hanlam still holds relevance among the Lotha couples as it indirectly benefits the newly married couple not only in terms of monetary help but through hanlam the couples are recognised and accepted by their kin, especially the groom is regarded as one of the kin members by the brides' paternal kins. Furthermore, it is the only traditional practice left in Lotha marriage ceremony. Finally, the continuation of the practice of Hanlam has not led to the curtailment of women's rights.